2006
DOI: 10.1136/bjo.2006.099598
|View full text |Cite
|
Sign up to set email alerts
|

The International Intravitreal Bevacizumab Safety Survey: using the internet to assess drug safety worldwide

Abstract: Aim: Off-label intravitreal injections of bevacizumab (Avastin) have been given for the treatment of neovascular and exudative ocular diseases since May 2005. Since then, the use of intravitreal bevacizumab has spread worldwide, but the drug-related adverse events associated with its use have been reported only in a few retrospective reviews. The International Intravitreal Bevacizumab Safety Survey was initiated to gather timely information regarding adverse events from doctors around the world via the interne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
154
0
9

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 499 publications
(175 citation statements)
references
References 22 publications
12
154
0
9
Order By: Relevance
“…These observations are in line with the reported literature [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18]. In our data, out of 187 ranibizumab injections there were 2 events (1.1%) of transiently elevated IOP of more than 30 mm Hg, which required administration of IOP-lowering drops.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These observations are in line with the reported literature [4,5,6,7,8,9,10,11,12,13,14,15,16,17,18]. In our data, out of 187 ranibizumab injections there were 2 events (1.1%) of transiently elevated IOP of more than 30 mm Hg, which required administration of IOP-lowering drops.…”
Section: Discussionsupporting
confidence: 82%
“…There were no reported cases of endophthalmitis in the PIER study [10]. According to the internet-based survey of Fung et al[ 15], the incidence of endophthalmitis after using intravitreal injections of bevacizumab was 0.01%. Cleary et al[ 12] also reported 1 case of endophthalmitis during the median follow-up of 5 months of 112 patients treated with bevacizumab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adverse events reported were corneal abrasion, lens injury, endophthalmitis, retinal detachment, inflammation or uveitis, cataract progression, acute vision loss, central retinal artery occlusion, subretinal haemorrhage, retinal pigment epithelium tears, blood-pressure elevation, transient ischaemic attack, cerebrovascular accident and death. None of the adverse event rates exceeded 0.21% [22]. These results are also confirmed by a 12-month follow-up study of 1,265 consecutive patients with various diagnoses, including exudative AMD, who received 4,303 intravitreal injections of bevacizumab [46].…”
Section: Discussionsupporting
confidence: 62%
“…This effect on the already damaged RPE, due to the age-related macular degeneration, may further deteriorate the junctions between the RPE cells and predispose to the development of an RPE tear. However, as this complication may as well occur during the natural course of CNV associated with PED or even after intravitreal injection of antiangiogenic drugs, other factors such as the contraction of the neovascular membrane or the pressure of the subpigment epithelium fluid may also contribute to the development of this complication [16,17,18]. …”
Section: Discussionmentioning
confidence: 99%